The IMIA History Working Group: Inception through the IMIA History Taskforce, and Major Events Leading Up to the 50th Anniversary of IMIA - Kulikowski, C. A.; Mihalas, G.; Greenes, R. A.; Yacubsohn, V.; Park, H.-A. (Yearbook of Medical Informatics, 2017)
Background: The 50th Anniversary of IMIA will be celebrated in 2017 at the World Congress of Medical Informatics in China. This takes place 50 years after the International Federation of Information Processing (IFIP) Societies approved the formation of a new Technical Committee (TC) 4 on Medical Information Processing, which was the predecessor of IMIA, under the leadership of Dr. Francois Grémy. The IMIA History Working Group (WG) was approved in 2014 to document and write about the history of the field and its organizations.Objectives: The goals of this paper are to describe how the IMIA History WG arose and developed, including its meetings and projects, leading to the forthcoming 50th Anniversary of IMIA.Methods: We give a chronology of major developments leading up to the current work of the IMIA History WG and how it has stimulated writing on the international history of biomedical and health informatics, sponsoring the systematic compilation and writing of articles and stories from pioneers and leaders in the field, and the organization of workshops and panels over the past six years, leading towards the publication of the contributed volume on the 50th IMIA Anniversary History as an eBook by IOS Press.Conclusions: This article leads up to the IMIA History eBook which will contain original autobiographical retrospectives by pioneers and leaders in the field, together with professional organizational histories of the national and regional societies and working groups of IMIA, with commentary on the main themes and topics which have evolved as scientific and clinical practices have changed under the influence of new insights, technologies, and the changing socio-economic, cultural and professional circumstances around the globe over the past 50 years.
Keywords: IMIA; History of International Biomedical and Health Informatics; History Working Group; IMIA 50th Anniversary